Big Book Media for Teaching Growth and Development of Living Things in Elementary School: Buku Besar Media untuk Mengajar Pertumbuhan dan Perkembangan Makhluk Hidup di Sekolah Dasar - Mufidah, Enik; Romadlon, Dzulfikar Akbar (Indonesian Journal of Education Methods Development, 2025)
General Background: Learning media play a critical role in enhancing the quality and engagement of science education in elementary schools. Specific Background: However, many educators still rely on conventional materials that fail to captivate students' interest, particularly in abstract topics such as the growth and development of living things. Knowledge Gap: There is limited utilization and evaluation of visually engaging media such as Big Book in this specific subject context. Aims: This study aimed to develop and evaluate a Big Book learning media to support the teaching of growth and development in living organisms for third-grade elementary students. Results: The development process employed the ADDIE model and involved 23 students at MI Muhammadiyah 02 Solokuro. Validation from experts yielded scores of 92% (content) and 95% (media design), while student and teacher responses reached 90% and 93%, respectively. Post-test scores increased significantly from 44% to 73%. Novelty: Unlike previous studies, this research applied the Big Book to a science theme rather than early reading skills, demonstrating its interdisciplinary potential. Implications: The Big Book was found to be pedagogically effective, increasing student motivation and comprehension, and is recommended for broader application in science instruction at the elementary level. Highlights: Enhances student interest and comprehension using visual and engaging media. Developed with the ADDIE model and validated by experts with high scores. Demonstrates significant improvement in learning outcomes post-intervention. Keywords: Big Book, Learning Media, Elementary Science, Student Motivation, Growth and Development